Sustainable market? The impact of downstream market concentration on high-quality agricultural development: evidence from China’s dairy industry - Yu, Zetian; Feng, Guang; Liu, Hao; Peng, Hua; Dong, Xiaoxia (Frontiers in Sustainable Food Systems, 2024)
The downstream concentration of agricultural products markets under the asymmetric competition pattern of the supply chain has a profound impact on upstream agricultural production. Is this centralized market structure sustainable and efficient? The study examines the effects and mechanisms of agricultural product downstream concentration on the high-quality development of agriculture using the dairy industry as an example. Panel data from 10 provinces in China from 2004 to 2021 were selected for analysis. Using Malmquist index, fixed effects model and other methods, the research results prove that: (1) Downstream dairy market concentration is unfavorable to upstream raw milk total factor productivity growth. However, there is scale heterogeneity in this negative effect, with a positive impact for small-scale farming and a negative impact on medium-scale and large-scale farming.(2) Downstream market concentration drives upstream raw milk total factor productivity growth through technical efficiency improvements and market demand expansion, but it also inhibits raw milk total factor productivity growth through mechanisms that squeeze production margins and impede technological progress.Negative mechanisms are the main effect. (3) Higher wages, higher raw milk prices and an improved ratio of concentrate to crude are all helping to mitigate the negative effects of downstream concentration to some extent, but net profit retention and a high proportion of fixed assets will further exacerbate the negative effects. To better address the challenges brought by the trend of downstream market concentration and promote high-quality agricultural development, this paper proposes three suggestions: enhancing the market position of dairy farmers, regulating monopolistic behavior of oligopolies and building a mechanism for linking interests.